Reg Bottini, 1940-1945
1945 1939-1945 "Reg Bottini, 1940-1945" [HFR0240], 1940-1945 Reg Bottini [1916-1999] was active in the Labour Party and became a political conscientious objector during the war. Bottini tried to get a job in the ARP Civil Defence but was rejected by 28 London Boroughs. He eventually found work in land drainage and agriculture, later joining the National Union of Agricultural Workers. In 1970, he became the Union's General Secretary and sat on the TUC General Council 1970-78. In 1980, he recorded his memories of the period for the Imperial War Museum. Bottini regarded the war as an imperial conflict and "opposed the war on grounds of working-class solidarity".